Let it grow - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Christophe Mabiala Mvika of the NGO Action for Community Development - ADEC (BP 94, Muanda, Bas Congo, Democratic Republic of Congo) reports 'we have now completed our experimental reforestation plot of 109 by 44 metres. We would like to expand into...